One‐way flexural shear tests on wide reinforced concrete slab segments with simple and intermediate supports. (16th December 2022) - Adam, Viviane; Schmidt, Maximilian; Hegger, Josef
Abstract: Flexural shear behavior, which mainly concerns reinforced concrete (RC) slabs without shear reinforcement, is usually investigated by means of simply supported, beam‐shaped specimens. Only few tests are available where the cross‐section properties correspond to a slab ( b ≫ h ) or the support conditions lead to moment and shear force distributions of multi‐span slab systems. The moment distribution in the vicinity of inner supports can decrease shear slenderness and, hence, increase shear strength. An increase in member width is also often associated with a beneficial effect on load bearing behavior. Firstly, the course of the shear crack changes along the width which, both, increases the crack face area, and potentially allows for an increased interlocking effect of the two crack faces. Secondly, a (wide) slab's ability to redistribute inner stresses in lateral direction can compensate inner irregularities. However, the likelihood of irregularities to occur after all, increases with increasing concrete volume, so larger member widths. A comparison of existing investigations shows that the findings are partly inconclusive. Also, no studies addressing the influence of the member width exist with tests in the vicinity of intermediate supports despite being the typical shear‐critical section in actual members. To address related open questions, an experimental campaign comprising 20 shear tests on slab segments without shear reinforcement was conducted. Essentially, member width ( b = 0.3 or 2.4 m) and support conditions were varied within the test program. Main goal of the experimental campaign was finding answers to the question whether one‐way flexural shear strength is influenced by the member's width. This has been addressed by generating results from pairs of tests which differed only in their width while having otherwise equal properties ( b / h ≈ 1.0 and b / h ≈ 8.5). Eight such pairs were tested featuring different shear span lengths, rotational restrains at the support and longitudinal reinforcement ratios. In contrast to other experimental campaigns, shear tests near inner supports were incorporated in the experimental program. On average, the gain in shear capacity of the wide members compared to the reference linear member was proportional to the increase in width. It can thus be concluded that linear (beam‐shaped) specimens are suitable for representing one‐way shear capacity of RC slabs. Enhanced shear response of actual slabs can rather be ascribed to beneficial effects from loading and support conditions which enable to partially activate two‐way stress distribution or compressive membrane action. Additionally, rare occurrence of damages in RC slabs is not only to be attributed to an underestimation of capacity but probably also to an overestimation of design load.